People and agrarian landscapes : an archaeology of postclassical local societies in the western Mediterranean - Quirós Castillo, Juan Antonio; Narbarte Hernández, Josu (Historical archaeologies series., 2023)
Provides an overview of the driving theories, methodologies and main topics that have been addressed to date regarding agrarian archaeology. The text is presented as an introduction for students, a critical reading guide for other scholars, and an informative instrument aimed at a wide audience.